Dominasi dan Deforestasi: Studi Kritis Antroposentrisme di Balik Gundulnya Gunung-Gunung di Bima - Nur Febriani; Muhammad Sarjan (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study examines the relationship between anthropocentrism and deforestation in the mountainous region of Bima. The dominance of an economy oriented toward corn commodities has shifted the function of forests from ecological spaces into objects of exploitation, often neglecting environmental sustainability. This research applies a qualitative approach using a descriptive case study method. Data were collected through literature review, sociological observation, and analyzed using verstehen and hermeneutic approaches to interpret the relationship between community perspectives on nature and ecosystem degradation. The findings show that anthropocentric values are reflected in development policies, weak law enforcement, and strong economic dependence on forest land expansion. These conditions contribute to environmental degradation, including soil erosion, loss of biodiversity, flooding, and prolonged drought. In addition, the limited integration of local wisdom, such as awig-awig, in forest governance weakens the protection of conservation areas. This study highlights the need for a paradigm shift toward ecocentrism by strengthening the role of indigenous communities, integrating ecological values into public policy, and developing community-based forest management models to balance economic needs and ecosystem sustainability.